Making the invisible visible: practical applications of visual metaphors in teaching and learning accounting. Issue 1 (2nd January 2020) - Schwartz, Nadia
Abstract: Current accounting graduates will be engaged in a constantly changing and visual world, and educators can help them by harnessing the power of visual metaphors. This article illustrates how hand-drawings by student groups can reveal negative perceptions of accountants as a potential career choice for new students, making such perceptions something to overcome. In addition, it shows how drawings can make novel and complex concepts more accessible for novice learners. The article demonstrates that student-generated drawings can be a tool to identify and dispel misconceptions in the learning of accounting. Finally, the article shows how drawings can aid in the teaching of difficult accounting concepts. Visual metaphor is a powerful interdisciplinary communication skill that is necessary in the field of accounting reporting. Educators and their students benefit from using hand drawing as active learning for developing visual intelligence in the field of accounting.